82 Evaluating effectiveness of intimate partner violence education in clinical clerkships. (19th September 2017) - Truong, Jenny; Jung, Dawn; Lucia, Victoria; Afonso, Nelia
Abstract : Background: Intimate Partner Violence (IPV), defined as any form of sexual, physical, or emotional harm perpetrated by a current or former partner or spouse, is a prevalent public health issue. Insufficient coverage of IPV education during medical school has contributed to many graduates who perceive IPV education as irrelevant to their future practices. An experiential IPV curriculum was integrated into three preclinical courses at Oakland University William Beaumont (OUWB) School of Medicine and its effectiveness was assessed with the Physician Readiness to Manage Intimate Partner Violence Survey adapted for healthcare students (PREMIS-HS). Results from an earlier iteration of this project showed an increase in IPV knowledge as well as overall self-confidence in the cohort's ability to address IPV issues in the future during the preclinical years. In contrast, the aim of this project was to assess the effectiveness of clerkships at IPV education during the clinical years of medical school. Methods: A cohort of medical students completed the PREMIS-HS during preclinical years. This cohort was asked to complete the survey again, along with an investigator-generated survey (Clerkships Contributions survey) regarding specific clerkship contributions to IPV education. Results: Results from the PREMIS-HS and Clerkships Contributions survey showed a further increase in IPV knowledge scores (30.9Â±3.5) in comparison to scores collected during preclinical years (26.1Â±4.0), with the most knowledge and skills gained during the obstetrics and gynaecology clerkship. Conclusion: Incorporating IPV education during clerkship years, in addition to preclinical years, will foster future generations of physicians with skills to appropriately screen and provide resources to patients affected by IPV.